rCitrusBBC: a bacterial resource to mine for new agricultural probiotics for citrus - Solaz-Rodenas, Lucía; Penyalver, Ramón (American Society for Microbiology, 2023)
A culture collection of 147 selected bacteria from the rhizospheric citrus microbiome is available at the Valencian Institute of Agricultural Research (València, Spain). The data include information on plant growth-promoting (PGP) traits published to date and the presence of PGP-related genes in the available genomes of the different bacterial species.